Epidemiological Behavior of Malaria on the Pacific Coast of the Department of Nariño, Colombia, 2003–2017 (2020)
The Pacific Coast of the department of Nariño is one of the Colombian regions most affected by malaria. Therefore, to understand more about the situation of the disease in the region, this study aimed to describe the epidemiological behavior of this disease in said region during the period of 2003–2017. Materials and methods: The study was a descriptive epidemiological research. Secondary information was sourced from Public Health Surveillance System. The study variables consisted of cases and deaths due to malaria, which was distributed by sex and age, between the years of 2003–2017. Student’s t-test was used to evaluate the disease’s behavior. Results: During the study period, there were 84,600 cases of malaria, with an annual average of 5,640; 57.9% (95% ci: 57.6–58.3) in men and 42.1% (95% ci: 41.7–42.4) in women. The prevalence presented marked variability. During the years of 2007, 2016, and 2017, rates were higher with 29.9, 31.1, and 39.5 cases per 1,000 inhabitants, respectively. Conclusions: The municipalities where the majority of the cases were concentrated were Tumaco, Roberto Payan, and Olaya Herrera. Moreover, the origin of the cases were located in low variability micro-territories that share typical eco-epidemiological conditions for the circulation of the vector. During the study period, 41 deaths were recorded, with an annual average of 3 cases, of which 75.6% (95% ci: 62.5–88.8) were male and 24.4% (95% ci: 11.2–37.5) were female, with cases being distributed without a statistical significance (t Student = 1.66; p = 0.10).